Zoledronic acid for adjuvant use in patients with breast cancer. Issue 3 (March 2011) - Ressler, Sigrun; Mlineritsch, Brigitte; Greil, Richard
Zoledronic acid, a nitrogen-containing bisphosphonate, is firmly established in the management of metastatic bone disease. It inhibits farnesyl diphosphonate synthase within the mevalonate pathway and, through this mechanism, is a potent inhibitor of osteoclast-mediated bone resorption. In addition, there are preclinical data suggesting that farnesyl diphosphonate synthase inhibition by zoledronic acid has anti-tumor effects in breast cancer. Adjuvant therapies for early breast cancer are associated with substantial decreases in bone mineral density. Results from three clinical trials, ABCSG-12, Z-FAST and ZO-FAST, indicate that the addition of twice-yearly zoledronic acid to standard adjuvant endocrine therapy in premenopausal and postmenopausal patients with hormone receptor-positive breast cancer prevents cancer treatment-induced bone loss. Moreover, it is becoming evident that it may also exert anticancer effects in an estrogen-deprived state in the adjuvant and neoadjuvant setting. However, long-term side effects need to be taken into consideration for treatment decisions.